Istilah pentadbiran dan perniagaan : Bahasa Inggeris- Bahasa Malaysia - Dewan Bahasa dan Pustaka (Kuala Lumpur : Dewan Bahasa dan Pustaka, 1992)
English-Malay terminology on business administration
English and Malay
2
Keywords: Management -- Dictionaries; Commerce -- Terminology; English language -- Dictionaries -- Malay